Knowledge, attitude and practices on dental caries and periodontal diseases of the health sciences students of the University of the Philippines Manila - Kalaw, Angela Vida T.; Liao, Sarah Jessica SP.; Paras, Keziah C.; Murjani, Bhabita V.; Alfaro, Arlene Cecilia A.
Oral health cannot be separated from one's health. As future healthcare professionals, it is every UP Manila health science student?s responsibility to provide holistic care to his or her patients. To be able to deliver holistic care, one should have knowledge on all aspects pertaining to health and this includes oral health.
The objective of the study was to determine the knowledge, attitude and practices of the health sciences students of the University of the Philippines Manila. A three-part self-administered questionnaire was administered to 218 graduating health sciences students during the 1st Semester of the Academic Year 2016-2017. The participating colleges were the College of Allied Medical Professions, College of Medicine, College of Nursing, College of Pharmacy and the College of Public Health. The questionnaire consists of 15 multiple choice questions on knowledge on dental caries, periodontal diseases and oral hygiene practices, 10 items on their attitude towards oral health in the form of a Likert scale and 9 multiple choice questions on their oral health practices.
Majority of the participants (N ≥ 50%+1) are knowledgeable on oral health practices and oral hygiene instructions; however, it is evident that several misconceptions regarding the disease process and recommended treatment for both diseases exist and have to be addressed. Results show that most participants are more knowledgeable on dental caries than on periodontal diseases. Seven out of 218 participants (3.21%) claimed that they did not know what gingivitis was, while 68 (31.19%) participants claimed that they did not know what periodontitis was. The association of both diseases to other systemic conditions seemed unclear to majority of the participants.
Results show that majority have a positive attitude towards oral health. One hundred and sixty-seven out of 218 (75.69%) participants strongly agree that brushing one?s teeth is as important as taking a bath. One hundred and fifty (68.81%) strongly agreed that their oral health has an effect on their systemic health. However, a significant number (24.31%) were quite reluctant to spend 1000 pesos to restore a single tooth.
The practices of most participants are congruent to those recommended in literature. One hundred and eighty-five (89.80%) participants brush their teeth at least twice a day. Eighty-five (41.26%) visit their dentists every 6 months, 28 (13.59%) participants visit the dentist only when symptoms arise. Most of the participants claim that their main sources of information on oral health are their private dentists (72.33%), the internet (62.14%) and the media (43.69%). Only 63 (30.58%) participants say that they learned about oral health through a subject in school.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Dental caries; Periodontal diseases